Digitalisasi dan Penyebaran Informasi dalam Organisasi Novo Club - Ardian; Hadi, Abdul; Salwahita, Aprilius Muthya; Yani, Afri (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2024)
This research examines the impact of digitalization on innovation and collaboration in the Novo Club organization, an initiative of PT Paragon Technology and Innovation that focuses on youth development. Based on Manuel Castells' theory of network society, this research explores how digitalization affects operational performance, member interactions, and the value of novelty generated. The research method used was descriptive qualitative with data collected through field observations and in-depth interviews with Public Relations staff at Novo Club Regional 8. The results showed that digitalization improves operational efficiency, facilitates access to information, and strengthens collaboration and innovation. Digital platforms used by Novo Club, such as social media, Zoom, and YouTube, enable better coordination and dynamic exchange of ideas, accelerate the innovation process and expand the community network. The findings enrich the literature on the implementation of digital technologies in youth-focused organizations and provide new insights into the role of technology in improving organizational performance and innovation.